Mentoring Style, Self-Description, and Academic Achievement in English Class - Simanungkalit, Ate Gueen; Rondonuwu, Joppi Jacobus (LPPM Universitas Advent Indonesia, 2020)
The intention of the study was to examine student mentoring, self-description, and academic achievement in a selected private university in Jakarta, Indonesia. There were 150 respondents in the study. The 2 instruments used for collecting data were adopted from Cohen (1995) for identifying the mentoring style of the mentors of the students, and from Marsh (1999) for identifying self-description of the students. The analysis of data employed descriptive statistics (independent t-test) as well as Chisquare, One-way ANOVA, and Two-way ANOVA. The research inquiries focused on the following issues: (1) identifying the mentoring style, self-description, and academic achievement of the students; (2) the relationship of mentoring style, self-description, academic achievement, and demographic profiles; and (3) the interactive effects—individual and joint—of mentoring style, self-description, and student academic achievement. The findings of the study showed that 2 mentoring styles were predominant among their mentors: relationship emphasis and mentor model; students perceived themselves with a self-description focused on spiritual values; and students had high academic performance. Both male and female students perceived similar mentoring styles among their mentors, while, 1st year and 2nd year students perceived mentoring style to be different among their mentors. In self-description, differences were found between genders while there was no difference found between 1st and 2nd year students. There was no difference found between gender and year of study in the academic achievement, the students showed high performance. Mentoring style and self-description did not have a significant individual or joint difference on academic achievement. Since the students, as a whole had high academic achievement, this study seemed to suggest that the different mentoring style did not have a difference on their academic achievement. However, that did not mean that mentoring did not work. On the contrary, it seemed that mentoring, regardless of style—based on the high academic achievement scores—did work. However, there was also the possibility that high achieving students might not need mentoring for improving their academic achievement.